“Evaluación de tres tecnologías en la producción de maíz negro (zea mays l.) iniap 199 racimo de uva en el campus Ceasa, Cotopaxi 2023.” - Guerrero Rojas, Oscar David (2023)
Corn (Zea mays L), is a plant primarily cultivated in the Ecuadorian highlands, although in recent years it has experienced a reduction in its production due to a lack of access to modern technologies. This joint research, in collaboration with the National Institute of Agricultural Research (INIAP), aimed to establish an alternative to maximize the yield of the black corn variety INIAP - 199 "Racimo de uva" at the CEASA of the Technical University of Cotopaxi. This was achieved through the implementation of three production technologies: plastic mulch management, INIAP's technological management, and conventional farmer management. Various variables were analyzed, including emergence, height, days to tasseling, days to dry harvest, yield of cobs with leaves in a dry state, yield of cobs without leaves, grain moisture percentage at harvest, dry seed weight, percentage of waste, and total crop yield. From the collected data, tables and graphs were generated to display the differences in the aforementioned variables. Specifically, plastic mulch achieved a yield of 12,919.3 kg/ha, being the highest among the three investigated technologies. The results indicated that plastic mulch technology demonstrated better agronomic performance in terms of germination, height, and compliance with parameters established by maize manuals in the highland region.